Karakteristik kimia dan organoleptik minyak goreng bekas hasil penyaringan dengan penambahan Vitamin E: The Chemiccal And Organoleptic Properties Of Used Coconut Oil Efficacy Of Filtration And Tocoferol Addition - Agustono Prarudiyanto; Eko Basuki; Ahmad Alamsyah; Dody Handito (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2015)
Replication of using coconut oil for frying many times may have negative impact on health. This research was to investigate the effect of filtration with activated carbon and addition of tocoferol on chemical and organoleptic properties of used coconut oil. The experiments were conducted in laboratory and arrangeed with Completely Randomized Design with 4 replications. The treatments were :V1 = addition of tocoferol 10+1 mg in used coconut oil 150+1 g.V2 = addition of tocoferol 20+1 mg in used coconut oil 150+1 g.V3 = addition of tocoferol 30+1 mg in used coconut oil 150+1 g.V4 = addition of tocoferol 40+1 mg in used coconut oil 150+1 g.V5 = addition of tocoferol 50+1 mg in used coconut oil 150+1 g.There are 20 experiments unit totally. Data was analyzed with analysis of variancees at 5 percent significant level. Polynomial ortogonal test was applied at the same significant level if there were found significantly difference among treatments of moisture content, rendemen, peroxide value, free fatty acid and iodium value and Least Significant Difference test for parameter of color and odor (Yitnosumarto, 1991). The result showed that no significant differences found on addition of tocoferol the used coconut oil. The moisture, free fatty acid and peroxide value of the oil tend to increase and decrease when it filtered with activated carbon. However, the iodium value was vise versa. The addition of tocoferol was unable to improve the oil quality. The oil without filtration had browniesh yellow colour, and become dark yellow with filltration using activated carbon. The oil odor was very unpleasent without filtration and rather unpleasent with filtration. The addition of tocoferol was uneffective to enhance the oil quality, but a little improvement of oil odor was found if it compared to the used oil with or without filtration. The rendemen of the used oil filtration was around 75,81 percent.